La construcción social del envejecimiento y de la vejez: Un análisis discursivo en prensa escrita (2002)
The article explores discursive productions about aging and old age in two Colombian newspapers between January and April 2001. Drawing on social systems and social representations theories, it poses that the media are a social system that deconstruct and (re)construct contents circulating in society serving the elaboration of social representations. Emphasis is made on the active role of systems and individuals in transforming this knowledge and (re)constructing the social reality of aging and old age. The analysis of media articles follows the notion of frames, from a sociocultural perspective. Four interpretative frames to talk about aging and old age are identified: (1) experiences and relations, (2) social security, (3) socioeconomic problems and challenges, and (4) health and illness. Results are discussed in terms of the preeminence of these frames to deal with the social reality of aging and old age.